Development trend of settlements in the South Transdanubian Region - Molnár, Tamás; Ilk, Balázs Ferenc (Acta Scientiarum Socialium, 2010)
Development is an important theoretical and practical concept; the definition of its level depends significantly on what kind of factors we use to measure it. According to most approaches, it cannot be measured with one single index number, because it is a multidimensional and „multiindicator” concept. Differences are more visible and characteristic in smaller units than they are in bigger ones; by examining smaller units (such as settlements or micro-regions) one can get a clearer sense of where a region stands, developmentally than one can in studying an entire country or region. Measuring development in terms of GDP is impossible at these levels, so it is necessary to apply an indicator that reflects it faithfully. The value of personal income tax per person is suitable for this, since the income side calculation of the GDP gives the same result as the production one gives. Defining the development in such a manner, we found big differences between settlements in the examined years (1993 and 2008). There were already considerable differences among the region's settlements in the population's income positions in the years following the political transformation. This was shown by the value of regional polarization indicators, the relative scattering, and the Hoover index's high concentration. We found a loose coherence between the size of the settlements (in terms of population) and the personal income tax per person. The differences which were already presented in 1993 increased toward the end of the analyzed period. Keywords: South Transdanubian Region, development, personal income tax per person, increasing differences Language: Hungarian
Keywords: South Transdanubian Region; development; personal income tax per person; increasing differences